ILLOCUTIONARY ACTS IN THE MOVIE MIDWAY (2019): A CULTURAL AND PRAGMATIC PERSPECTIVE - Reinaldy Christian Panduputra; Deden Novan Setiawan Nugraha (SAMPURASUN, 2024)
This study observes the illocutionary acts in the film "Midway" (2019) through the point of view of pragmatics and cultural context. By applying Austin’s and Leech’s speech act theory, the research identifies and categorizes various illocutionary acts and their functions performed by characters throughout the film. This research uses qualitative method in analyzing the movie. The analysis highlights how these acts contribute to the narrative and character development. In addition, the study examines the cultural and historical settings depicted in the film, considering how they influence and shape the illocutionary acts. This dual approach uncovers the interplay between language, culture, and context, providing a deeper understanding of communication dynamics in "Midway." With the types of illocutionary acts proposed by Austin, based on 8 data found, 3 data are Behabitive (37.5%), 1 data is Commissive (12.5%), 4 data are Exercitive (50%), 0 data is Verdictive (0%), and 0 data is Expositive (0%). With the functions of illocutionary acts proposed by Leech, based on 8 data found, 1 data is collaborative (12.5%), 4 data are convivial (50%), 3 data are competitive (37.5%), and 0 data is conflictive (0%). The research also brings 8 data contain practice (100%), 8 data contain perspective (100%), and 0 data contains product (0%).